PD-L1 Immunohistochemistry Comparability and Their Correlation with Clinical Characteristics in NSCLC - Chiao-En Wu; Ching-Fu Chang; Liao Kou-Sheng; Ju Chiang; Shih-Wei Lee; Yu-Chi Chiu (Analytical Cellular Pathology)
Background. PD-L1 expression is an important predictive factor of response to therapy with immune checkpoint inhibitors (ICIs). This study was designed to retrospectively analyze the concordance of PD-L1 measurements using three different assays (Dako22C3, Dako28-8, and SP142) in NSCLC patients and to find possible predictors of high PD-L1 expression. Materials and Methods. Data of 144 patients with histologically confirmed NSCLC and available PD-L1 measurements treated at the Taoyuan General Hospital from 2018 to 2019 were retrospectively reviewed in the study. Patients’ characteristics, including age, sex, clinical stage (T, N, and M) of NSCLC (AJCC, 8th edition), and EGFR/ALK alterations, were analyzed for association with PD-L1 expression. Results. Measurements of PD-L1 expression levels with Dako22C3 and Dako28-8 were comparable while SP142 showed lower levels of PD-L1 expression. The overall agreement between Dako22C3 and Dako28-8 was 82.2% and 91.6% for both 1% and 50% TPS cut-offs, respectively. The above findings were confirmed by Cohen’s kappa. In addition, we found that PD-L1 expression was significantly associated with advanced N stage but not with T and M stages. Conclusion. Dako22C3 and Dako28-8 showed comparable results in assessing PD-L1 levels. Future prospective studies are needed to validate these findings. N stage may be a good predictor for PD-L1 expression.